The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/pmj.21456
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Portfolio Management as a Subset of Dynamic Capabilities: Measurement and Impact on Innovative Performance

Abstract: Innovation portfolio management has been touted as a new dynamic capability following the evolution of team‐ and project‐based organizational forms. In this article, we conceptualize innovative dynamic capabilities as a multidimensional construct that comprises distinct but related aspects in managing innovation. We test our model, which links this capability to innovative performance by using survey data from a sample of 923 firms. We find empirical support for our conceptualization and its impact on firm inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 90 publications
1
35
0
2
Order By: Relevance
“…Atentos ao fato de que a capacidade de inovação possui natureza multidimensional quando componente de capacidades dinâmicas (Wang, & Ahmed, 2007;Sicotte, Drouin, & Delerue, 2015), adotou-se a abordagem desenvolvida por Camisón e Villar-López (2014) para medir a capacidade de inovação, que utiliza medidas de mensuração de inovação de produto, inovação de processo e inovação organizacional (práticas de negócios, inovação no local de trabalho e novos métodos organizacionais no relacionamento externo).…”
Section: Capacidade De Inovaçãounclassified
See 1 more Smart Citation
“…Atentos ao fato de que a capacidade de inovação possui natureza multidimensional quando componente de capacidades dinâmicas (Wang, & Ahmed, 2007;Sicotte, Drouin, & Delerue, 2015), adotou-se a abordagem desenvolvida por Camisón e Villar-López (2014) para medir a capacidade de inovação, que utiliza medidas de mensuração de inovação de produto, inovação de processo e inovação organizacional (práticas de negócios, inovação no local de trabalho e novos métodos organizacionais no relacionamento externo).…”
Section: Capacidade De Inovaçãounclassified
“…A literatura aponta que um desempenho superior pode ser alcançado quando as organizações engajam-se a uma gama de atividades voltadas à inovação (Piening, & Salge, 2015) caracterizada como um processo de desenvolvimento de novas ideias (Sicotte, Drouin, & Delerue, 2015), sendo a capacidade de inovação um recurso-chave (Lawson, & Samson, 2001). Estudos argumentam que empresas excelentes investem e estimulam a capacidade de inovação a partir do qual executam de modo eficaz os processos, levando a inovação em produtos, serviços e negócios, proporcionando melhores resultados ao desempenho (Yesil, Büyükbese, & Koska, 2013 (Gomes, Machado, & Alegre, 2014).…”
Section: Introductionunclassified
“…Innovation capability is an organization's ability and competence to initiate and carry out innovation processes -an adaptation of David Teece's concept of dynamic capabilities (Teece and Pisano 1994;Teece 2014; see also Barreto 2010;Sicotte et al 2014). More specifically, innovation capabilities manifest themselves in the processes of an organization which uses its resources (Eisenhardt and Martin 2000) to initiate and carry out innovations.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas Steiber and Alänge's (2013) study on Google revealed that learning was vital for current products and process improvements than new innovations, Sicotte et al (2014) found that innovation portfolio management need to build skills where learning would help them to be ahead of the competitors.…”
Section: Organisational Learningmentioning
confidence: 99%